Reflections on Reflection: Clarifying and Promoting Use in Experienced Coaches - Nash, Christine; MacPherson, Alan C.; Collins, Dave (Frontiers in Psychology, 2022)
Background: We draw on the work of established scholars reflective practice who highlight its importance as a key cognitive skill for professionals to hold. While the substantive effect of engaging in reflective practice is emphasised in the literature, apparently coaches only spend a limited time learning about and engaging with it. Objectives: This study was conducted in two parts: Part 1 examined coaches’ knowledge of reflective practice and ascertained their perceived lack of value and use of reflective practice within their coaching. In response to the unexpected findings in Part 1, in Part 2 we instituted an educational intervention to further these participant coaches’ knowledge of RP and facilitate its integration into their coaching practice Design: The present study utilised a mixed method design with semi-structured interviews being conducted in Part 1. A coach development reflective programme inspired by Ericsson and Simon’s (1993) Stimulated Recall was implemented in Part 2. Participants: Twelve high level coaches were interviewed about their reflective practices in Part 1. In Part 2, the same coaches agreed to participate in the educational intervention for the duration of the project. Results: Findings from Part 1 revealed an interesting paradox: coaches demonstrated a lack of appreciation for reflective practice yet recounted the positive influence that specific events and individuals had on their practice. In Part 2, to fully develop RP with the present cohort an educational intervention was conducted. While watching videos of their own practice, coaches initially required lots of prompts from the lead interviewer to facilitate a deep and meaningful discussion of their practice. During the latter stages of the intervention, however, participants were less dependent on questions and prompts. Conclusions: In part 1 the coaches in this study did employ reflection, although they did not label it as such. The qualitative evidence we have gathered enables us to suggest that it is the combination of how to reflect, and against what criteria that makes RP a powerful tool to develop expertise which it has the potential to be. Importantly, however, additional coach education input is necessary for these benefits to be fully realised.